Career preferences among nursing students in Institut Sains Dan Teknologi Darul Takzim (INSTEDT) / Dorice Tra Liam - Liam, Dorice Tra (Faculty of Business and Management, 2018)
The purpose of this study is to examine the relationship between intrinsic motivation, extrinsic motivation, third parties, career exposure and career preferences. The study has taken place in Institut Sains dan Teknologi Darul Takzim (INSTEDT) that located in Bandar Penawar, Johor. This was done my finding out factors influencing career preferences among nursing students in INSTEDT. The target respondents are nursing students from Semester 1 until Semester 6. Total population for this study is 250 and sample size is 152 respondents. Judgment or purposive sampling technique is used for this study. The researcher distributed the questionnaires through Google docs and the respondents have been given 2 weeks to answer the questionnaire. The data measures using frequency analysis, descriptive analysis, reliability analysis, hypothesis testing, pearson correlation coefficient, and multiple regression analysis. The study found that intrinsic motivation is the most influential factor affecting career preferences among nursing students in INSTEDT.